The impact of chemical modelling on turbulent premixed flame acoustics. (8th March 2021) - Brouzet, D.; Talei, M.; Brear, M.J.; Cuenot, B.
Abstract: Abstract : Direct numerical simulations are used to study the impact of chemical modelling on the flame dynamics and the sound generated by three-dimensional, turbulent, premixed methane/air jet flames. The semi-global BFER mechanism from Franzelli et al. ( Combust. Flame, vol. 159, issue 2, 2012, pp. 621–637) and the more complex skeletal COFFEE mechanism from Coffee ( Combust. Flame, vol. 55, issue 2, 1984, pp. 161–170) are considered. A more wrinkled flame is observed at downstream locations when using the COFFEE mechanism, demonstrating stronger flame/turbulence interaction. This flame also has a significantly lower acoustic power even though it features more acoustic output at high frequencies. The former is shown to arise from lower fluctuations of the heat release rate, whilst the latter is caused by the COFFEE mechanism creating more wrinkled flame surfaces. These results suggest that the accurate simulation of the noise emitted by turbulent premixed flames requires a chemical mechanism that ensures two main features: the heat release rate profile is important for modelling the overall sound amplitude and low frequency acoustics, whilst the flame/turbulence interaction impacts the higher frequency sound.